Peculiarities of Aerobic Development in Kayak Rowers Preparing for 1000 m Event (Baltic Journal of Sport and Health Sciences, 2013)
Research  background  and  hypothesis.  Lithuanian  scientific  publications  mostly  deal  with  kayak  rowers’ preparation for 200 and 500 m events, while 1000 m event is hardly analyzed yet. Research aim was to project scientifically based program of kayak rowers’ preparation for 1000 m event, which is to develop aerobic capacity in different mezo-cycles, and to evaluate its efficiency.Research methods. Preparation of kayak doubles crew members was investigated; the athletes were the 5 th  place winners of 2013 World Cup II event. The carried out training load for aerobic capacity development was divided into 5 zones of intensity. During training sessions, computer program Garmin Connect measured the distance and speed of a boat, as well as athletes’ heart rate (HR). Athletes’ aerobic capacity at critical intensity level (CIL) and anaerobic threshold (ANT) was established using gas analyser ‘Oxycon Mobile’. Research results. As the research showed, the kayak rowers in mezzo-cycles of both preparatory and competition periods carried out very little training load in the fifth zone of intensity. Considerable is also the fact that during competition period, in mezzo-cycle, the total number of kilometres decreased from 218 to 158 km. Discussion and conclusions. The research demonstrated that training workloads in the first and the second zones for elite kayak rowers preparing for 1000 m event in the first mezzo-cycle of competitive period were diminished comparing to the workload carried out in the preparatory period, while the amount of workload in the fourth zone was considerably increased. Adaptation of the two elite athletes to applied training loads is different, although they were following the same program. Due to this fact, the training process of those athletes is recommended to be given more individual approach, though they are rowing one boat.Keywords: kayak rowing, preparatory and competitive periods, training mezzo-cycles, aerobic capacity.